Multimodal [18F]FDG PET/CT Is a Direct Readout for Inflammatory Bone Repair: A Longitudinal Study in TNFα Transgenic Mice. (30th July 2019) - Hayer, Silvia; Zeilinger, Markus; Weiss, Volker; Dumanic, Monika; Seibt, Markus; Niederreiter, Birgit; Shvets, Tetyana; Pichler, Florian; Wadsak, Wolfgang; Podesser, Bruno K; Helbich, Thomas H; Hacker, Marcus; et al.
ABSTRACT: In rheumatoid arthritis (RA), chronic joint inflammation leading to bone and cartilage damage is the major cause of functional impairment. Whereas reduction of synovitis and blockade of joint damage can be successfully achieved by disease modifying antirheumatic therapies, bone repair upon therapeutic interventions has only been rarely reported. The aim of this study was to use fluorodeoxyglucose ([ 18 F]FDG) and [ 18 F]fluoride µPET/CT imaging to monitor systemic inflammatory and destructive bone remodeling processes as well as potential bone repair in an established mouse model of chronic inflammatory, erosive polyarthritis. Therefore, human tumor necrosis factor transgenic (hTNFtg) mice were treated with infliximab, an anti‐TNF antibody, for 4 weeks. Before and after treatment period, mice received either [ 18 F]FDG, for detecting inflammatory processes, or [ 18 F]fluoride, for monitoring bone remodeling processes, for PET scans followed by CT scans. Standardized uptake values (SUVmean ) were analyzed in various joints and histopathological signs of arthritis, joint damage, and repair were assessed. Longitudinal PET/CT scans revealed a significant decrease in [ 18 F]FDG SUVs in affected joints demonstrating complete remission of inflammatory processes due to TNF blockade. In contrast, [ 18 F]fluoride SUVs could not discriminate between different severities of bone damage in hTNFtg mice. Repeated in vivo CT images proved a structural reversal of preexisting bone erosions after anti‐TNF therapy. Accordingly, histological analysis showed complete resolution of synovial inflammation and healing of bone at sites of former bone erosion. We conclude that in vivo multimodal [ 18 F]FDG µPET/CT imaging allows to quantify and monitor inflammation‐mediated bone damage and reveals not only reversal of synovitis but also bone repair upon TNF blockade in experimental arthritis. © 2019 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.